Information wars : How we lost the global battle against disinformation & what we can do about it - Stengel, Richard (Grove Press, 2019)
From former TIME editor and Under Secretary for Public Diplomacy and Public Affairs Richard Stengel, Information War is the first and only insider account exploring how the U.S. tried -- and failed -- to combat the global rise of disinformation that eventually spilled into the 2016 election